The Effect of Scientific Approach on Junior High School Students’ Scientific Creativity and Cognitive Learning Outcomes (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
This study investigates the effects of using scientific approach-based learning tools on students' scientific creativity (SC) and cognitive learning outcomes (CLO). This study employed a one-group pretest-posttest design that involved 70 students of Maduran Junior High School Lamongan. Students' SC and CLO were collected by using fifteen essay tests and analyzed descriptively and statistically. The result shows that (1) the proportion of lesson plan (RPP) implementation was highly excellent, (2) students’ responses were quite strong to the learning activities, and (3) students' SC and CLO improved moderately. Statistically, students’ SC and CLO stated significantly different after treatment (p < 0.05) and positively correlate (Sig. > 0.7). Based on the study findings and discussion, it can be concluded that the scientific approach significantly affects students’ SC and CLO.